STUDIES ON SOME ASPECT^ OF THE BIOLOGY OF THE COMMON ANCHOVY, THRISSOCLES MYSTAX (BLOCH & SCHNEIDER) - Venkataraman, G (Indian Journal of Fisheries, 2015)
The anchovies form an important fishery along the Malabar Coast and contribute considerably to the fish catches during certain seasons of the year and especially during the lean years lor sardines. Of the 7 species of anchovies recorded along the west coast, i,Thrissocles mystax is the most common and is caught abundantly in the cdinmercial hauls. It has a wide distribution and is known to occur in the seas of India, Malay Archipelago and China. It attains a maximum length of 205 mm.